2015
DOI: 10.1111/apa.13090
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate vitamin D levels are associated with culture positive sepsis and poor outcomes in paediatric intensive care

Abstract: Children admitted to the PICU with suspected sepsis had lower 25OHD than controls and inadequate 25OHD status was associated with confirmed sepsis and poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26). Despite the rapidly increasing volume of evidence linking 25(OH)D deficiency with ICU morbidity and mortality over the past 10 years (1-4, 6-8, 10, 11, 27, 28), the question of whether vitamin D repletion will improve clinical outcomes in critical illness remains unclear.…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 40%
“…Additional studies of vitamin D deficiency in the pediatric intensive care unit (ICU) (PICU) population have reported a prevalence of between 30 and 86% (18)(19)(20)(21). We found lower 25(OH)D levels to be associated with greater illness severity (22); other pediatric critical care studies have confirmed this finding (19,21,23,24), although equal numbers have reported no correlation with illness severity or ICU outcomes (18-20, 25, 26). Despite the rapidly increasing volume of evidence linking 25(OH)D deficiency with ICU morbidity and mortality over the past 10 years (1-4, 6-8, 10, 11, 27, 28), the question of whether vitamin D repletion will improve clinical outcomes in critical illness remains unclear.…”
Section: Low Serum Concentrations Of Total 25-hydroxyvitamin D (25[oh]d)mentioning
confidence: 40%
“…Further, VDD was associated with higher illness severity, multiple organ dysfunction, and mortality across these studies. Six of these studies focused on or separately analyzed children with sepsis [433][434][435][436][437]. Three studies reported a greater need for vasoactive agents in VDD children [433][434][435], although mortality across these six studies was not associated with VDD [433][434][435][436][437] (Supplemental Table 26, Supplemental Digital Content 1, http://links .lww.com/PCC/B139).…”
Section: We Suggest Against the Acute Repletion Of Vitamin D Deficienmentioning
confidence: 99%
“…Several studies investigated the prevalence of VitD deficiency in intensive care unit (ICU) patients and found that most critically ill patients had very low levels of VitD [18][19][20] . Furthermore, VitD deficiency was associated with increased mortality in septic adult [21][22][23] and paediatric 24 patients.…”
Section: Introductionmentioning
confidence: 99%